Awareness and Use of E-Resources in Abdullahi Fodiyo Library Complex among the Academic Staff Members of Usmanu Danfodiyo University, Sokoto - Kpakiko, Mohammed M.; Sadiku, Shaibu A. (MiddleBelt Journal of Library and Information Science, 2015)
The paper investigated the level of awareness and usage of available electronic information resources in Abdullahi Fodiyo Library Complex and its impact on the teaching and research performances of the academic staff members of Usmanu Danfodiyo University, Sokoto. It examined five faculties namely: Social Sciences, Sciences, Law, Health Sciences and Education. The objective of the paper is to find out the level of awareness on the existing e-resources in the library, e-resources frequently used, level of satisfaction and challenges encountered while using the e-resources. Adaptive structuration theory (AST) of the media was used as the theoretical perspective. Survey technique was used using the questionnaire as instrument which was randomly distributed among respondents in the five faculties. It was concluded that although respondents use e-resources frequently, which is characterised by a number of challenges such as network down time, slow download, and erratic power supply among other challenges. The paper recommended for an inclusion of a specialised online bibliographic database on the library portal, develop adequate awareness programmes to sensitize the academic staff on available e-resources and the existence of a library portal. The paper also suggested user training as well as regular revision of network infrastructure to meet the ever-growing user demand within and outside the institution.